1997
DOI: 10.1021/ac9604550
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Hydrofluoric Acid Species by Chemical-Modeling Regression of Near-Infrared Spectra

Abstract: Near-infrared spectroscopy in the wavelength region 800−1100 nm has been applied to the measurement of aqueous solutions of hydrofluoric acid over the concentration range 0.01−2.65 M and the pH range 2−13. The analysis is based on the detection of subtle perturbations of the water spectrum which result from the presence of the acid and other species in solution. Spectral characterization of the hydrofluoric acid system was performed using a spectrophotometric titration and multivariate model-based regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…CMR is a multivariate analysis technique in which a set of orthogonal eigenvectors, computed from absorbance spectra, is iteratively fit to a chemical model by adjusting the model parameters. Thompson and colleagues demonstrated the utility of CMR for estimating the equilibrium constants and species concentrations for the hydrofluoric acid system (Thompson et al 1997). In the case of pH measurements using an indicating dye, the calibration spectra would consist of constant-concentration dye solutions buffered to span a desired pH range, and the chemical model is derived from the HendersonHasselbalch and mass-balance equations for the system: 6) where is the total concentration of the dye in solution.…”
Section: Discussionmentioning
confidence: 99%
“…CMR is a multivariate analysis technique in which a set of orthogonal eigenvectors, computed from absorbance spectra, is iteratively fit to a chemical model by adjusting the model parameters. Thompson and colleagues demonstrated the utility of CMR for estimating the equilibrium constants and species concentrations for the hydrofluoric acid system (Thompson et al 1997). In the case of pH measurements using an indicating dye, the calibration spectra would consist of constant-concentration dye solutions buffered to span a desired pH range, and the chemical model is derived from the HendersonHasselbalch and mass-balance equations for the system: 6) where is the total concentration of the dye in solution.…”
Section: Discussionmentioning
confidence: 99%
“…At this point we are able to point out the distinctive nature of the NaF solution. Previous ab initio simulation study of fluorine hydration, [27] as well as mid-infrared [28] and NIR [29] studies of hydrofluoric acid, showed uncertainties in the hydration structure and dissociation configuration of F and HF, as they are accompanied by the formation of various hydrogenbonded complexes (HF, HF 2 À , [H 3 O·F] À ) with exceptionally strong OÀH···F hydrogen bonding. Our measurement of pH ( % 7.98 at the 1.2 m level) suggested that significant ionization does take place and that we do not observe freely hydrated F À ions in the solution.…”
Section: Pure-water-subtracted Spectramentioning
confidence: 99%
“…Besides the advantages of NIR spectroscopy, there are drawbacks to it, including its low sensitivity and the characteristic broadness of absorption bands, which often results in overlapped spectra (Thompson et al, 1997). For such spectra, multivariate calibration methods, such as principal component analysis (PCA), discriminant analysis (DA), soft independent modeling of class analogy (SIMCA), artificial neural networks (ANN), discriminant partial least-squares (DPLS), and so on, open the possibility to unravel and interpret the optical properties of the sample and allow a classification without the use of chemical information (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%